Forming a Harmonious Society: Hadith Sahih Bukhari's Approach to Handling Sociopolitical Issues in Malaysia - Latifah Abdul Majid (Sekolah Tinggi Ilmu Ushuluddin (STIU) Darul Hikmah, 2024)
Malaysia, a sociopolitical which consists of various religions, several nations, and peoples. Sociopolitics experiences tensions and challenges in managing social pluralism. Issues that arise in the face of the challenges of diversity in society experience tension, including gambling attitudes between groups, ethnic identities that hinder the integration and diversity of thoughts, beliefs, and habits of groups. This requires an alternative for building a society that leads to harmony, security, and positive interaction between people, religions and cultures, and nations. Therefore, achievements in developing a pluralistic society are based on elements of political stability, societal cohesion, and state harmony. This study uses qualitative methods by examining data and analyzing documents, including paying attention to current sociopolitical issues. The main data for the study uses the Sahih al-Bukhari book. The objective of this study is to analyze the solution of fostering a pluralistic society from the perspective of the hadith of Sahih al-Bukhari by applying the values of harmony in a pluralistic society, the value of political stability, the value of social justice, and fostering the value of social cohesion. The results of the study found that values such as harmony, stability, justice, and social cohesion guarantee a state that is based on the Malaysian nation-state. The implications of the study find that sociopolitical values help strengthen the relationship between a pluralistic society and political leaders, as well as ensuring social harmony and stability in Malaysia.